Структурная адаптация программных систем: анализ состояния проблемы и некоторые подходы к ее решению - Ткачук, Н. В.; Нагорный, К. А. (Eastern-European Journal of Enterprise Technologies, 2020)
Adaptive approaches for software design were reviewed and classified. Problem of structure adaptation was formulated, existing methods of it’s solution were cited, cybernetic approach based on post object-oriented technologies was proposed